Design and implementation of a hybrid RFID-GPS human tracking system / Muhammad Sadiq Rohei - Muhammad Sadiq , Rohei (2019)
In pervasive computing research, object tracking and specification is an emerging trend. Researchers have been working on ways to allow people to work safely and freely within certain environments. With the use of RFID technology, objects can become part of real-world communication indoors while GPS tracking accommodates outdoor environments. The RFID-GPS hybrid system uses features from both technologies to provide a robust location tracking system that covers a wide variety of applications, including the tracking of animals, vehicles or people. This can be used to improve the safety of important or vulnerable members of society, particularly in developing countries where persecution and kidnapping are rampant. For example, the rate at which medical practitioners are being kidnapped has hit 41%, which makes it imperative for this study to develop an application that facilitates a safer commute and possible monitoring. To this end, an approach based on comprehensive studies is proposed using simulation to evaluate the suitability of epidermal RFID tags (implanted under the skin of participants) in a hybrid RFID-GPS tracking system operating under the IoT paradigm. The study's model aims at improving the safety of doctors by assigning them IDs using unique UHF passive RFID tags that operate at a frequency of 868 MHz, which is regionally altered. The RFID tag was designed and simulated through technical methodology using Matlab, the Simulink environment and relevant system middleware prototyped through the Microsoft ASP MVC platform. Using these technologies, the GPS coordinates of the research-based area and the virtual floor plan of the unified centre are included in the system. This was to allow end users to visualise system performance on Google Maps and within the building parameters. The results showed that the simulated tag had a high transmission rate with a corresponding factor of γ =0.6, almost 1.57 dBi power gain, and a reading distance of nearly 4 metres. The system's middleware contains outstanding features such as innovative, fast and accurate real-time location tracking. It has been proven to guarantee the safety of doctors in hospitals/fieldwork, and is ready for actual establishment at a unified centre.